Biosilver nanoparticle interface offers improved cell viability - VanOosten, Sarah Kay; Yuca, Esra; Karaca, Banu Taktak; Boone, Kyle; Snead, Malcolm L.; Spencer, Paulette; Tamerler, Candan (ICE PUBLISHING, 2016)
Silver nanoparticles (AgNP) are promising candidates for fighting drug-resistant infections because of their intrinsic antimicrobial effect. The design of high-yield antimicrobial molecules may inadvertently cause variation in host cells' biological responses. While many factors affect AgNPs' efficacy, their surface is exposed to the biological environment and thus plays a critical role in both the preservation of antimicrobial efficacy against pathogens and the modulation of host cells cytotoxicity. This work investigated an engineered biomimetic interface approach to controlling AgNP surface properties to provide them a competitive advantage in a biological environment. Here, a fusion protein featuring a silver-binding peptide (AgBP) domain was engineered to enable self-assembly and track assembly by a green fluorescent protein (GFP) reporter. Following AgNP functionalisation with GFP-AgBP, their antimicrobial and cytotoxic properties were evaluated. GFP-AgBP binding affinity to AgNPs was evaluated using localized surface plasmon resonance sensing. The GFP-AgBP biomimetic interface on AgNPs' surfaces provided sustained antibacterial efficacy at low concentrations based on bacterial growth inhibition assays. Viability and cytotoxicity measurements in fibroblast cells exposed to GFP-AgBP protein-functionalised AgNPs showed significant improvement compared to controls. Biointerface engineering offers promise towards tailoring AgNP antimicrobial efficacy while addressing safety concerns to maintain optimum cellular interactions.
Keywords: anti-microbial; biointerface; nanoparticles; QUATERNARY AMMONIUM-COMPOUNDS; SILVER NANOPARTICLES; ANTIMICROBIAL POLYMERS; ANTIBACTERIAL ACTIVITY; CHIMERIC PEPTIDES; CYTOTOXICITY; PROTEIN; AGENTS; TOXICITY; RESISTANCE; Chemistry; Materials Science